2015
DOI: 10.1001/jamaneurol.2015.2614
|View full text |Cite
|
Sign up to set email alerts
|

A Thalamocortical Mechanism for the Absence of Overt Motor Behavior in Covertly Aware Patients

Abstract: IMPORTANCE It is well accepted that a significant number of patients in a vegetative state are covertly aware and capable of following commands by modulating their neural responses in motor imagery tasks despite remaining nonresponsive behaviorally. To date, there have been few attempts to explain this dissociation between preserved covert motor behavior and absent overt motor behavior. OBJECTIVES To investigate the differential neural substrates of overt and covert motor behavior and assess the structural int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 66 publications
2
84
1
Order By: Relevance
“…Hence, a reasonable argument could be made that if someone demonstrated evidence of consciousness via motor imagery that they should be able to engage intentional motor acts 13 . However, a recent study suggested that a possible biomarker for absent intentional movement in covertly aware patients was the selective structural damage to thalamocortical motor circuits 16 . In line with this proposition, we found that voluntary motor imagery and execution were dissociable (one could be present in the absence of the other).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a reasonable argument could be made that if someone demonstrated evidence of consciousness via motor imagery that they should be able to engage intentional motor acts 13 . However, a recent study suggested that a possible biomarker for absent intentional movement in covertly aware patients was the selective structural damage to thalamocortical motor circuits 16 . In line with this proposition, we found that voluntary motor imagery and execution were dissociable (one could be present in the absence of the other).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also lack a precise neural account for the paradoxical impairment of purposeful motor behavior in covertly aware patients 1315 . A previous study examined the importance of selective structural damage to thalamocortical motor fibers as an explanation for the lack of intentional movement in a single VS/UWS patient with identified covert consciousness 16 . Thus, whether structural damage is a necessary condition for the dissociation between covert (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients may become unable to respond to stimuli despite still having conscious experiences 2, 3. This may happen because of motor or executive function impairments4, 5 and/or because of sensory disconnection from the environment 6. States of disconnected consciousness can occur in healthy subjects during dreaming7 and some forms of anesthesia,8 and may result from severe brain injury 9.…”
mentioning
confidence: 99%
“…They are able to follow command(s) by modulating their neural responses in motor imagery (MI) tasks reflected in fMRI findings. Study by Fernadez-espejo et al showed, that they have intacted thalamus, but damaged excitatory coupling between the thalamus and primary motor cortex [52]. But role of certain brain areas (bilateral occipital areas, left parahippocampus, other temporal and frontal areas, etc.)…”
Section: Approaches To Communication Disorders In Docmentioning
confidence: 99%